“To Listen to the Language of Nature and to Act Accordingly” :: Natural Law as Beacon guiding to Human Flourishing and Ecological Civilization - Gassner, Franz (Orientis Aura: Macau Perspectives in Religious Studies, 2021)
The article sets off from a speech given by Benedict XVI in the German Bundestag in 2011, where he requested an ecological learning process to aim at sustainable human development. Appreciating the Ecological Movement, he asked to learn to listen to Nature’s language and act accordingly, which he applies analogically to “human ecology”. The article bridges elements of “Listening to Nature” and the Natural Moral Law Tradition in Benedict’s speech and in Francis’ Encyclical Letter Laudatu Si’ inview of serving human flourishing in an ecological civilization. Keywords: Natural Moral Law; Nature, Laudatu Si’, Benedict XVI, Francis; Ecological Civilization/生態文明, Sustainable Development, Ecology of Man.